Hubungan Self-Esteem (Harga Diri) dengan Perilaku Narsisme Pengguna Media Sosial Instagram pada Siswa SMA - Cici Guspa Dewi; Yulidar Ibrahim (Universitas Negeri Padang, 2019)
This research is motivated by a phenomenon that occurs in the field that the number of students using Instagram social media has narcissistic behavior, and one of the factors that influence narcissistic behavior is self-esteem. Students who have narcissistic behavior usually have low self-esteem because students have a need to get appreciation and appreciation for the formation of self-esteem, and this is the reason individuals use social media, especially Instagram, to fulfill all those needs. This study aims to 1) describe the self-esteem of students, 2) describe the behavior of narcissism instagram social media users in students, 3) test the significance of the relationship between self-esteem and the narcissism behavior of instagram social media users in students. This study uses a quantitative method with a descriptive correlational approach. The subject of this study was 50 students of SMA Negeri 1 Gunung Talang who were identified as students who had a tendency to narcissistic behavior. The instruments used were (1) inventory of self-esteem, (2) questionnaire narcissism behavior on instagram social media users with a Likert Scale model. Data analysis techniques used descriptive and correlational analysis techniques using computer program assistance Product and Service Solution (SPSS) version 20.0. Research findings show that (1) student self-esteem is in the low category, (2) narcissism behavior of instagram social media users are in the narcissism category, (3) there is a significant negative relationship between self-esteem and the narcissistm behavior of instagram social media users on students with a correlation coefficient of -0.548 and a significant level of 0,000.